Sagnac ring and photonic crystal fiber structure refractive index sensor with high birefringence and low temperature sensitivity - Liu, Zhiying; Li, Hao; Zhang, Zhiwen (Frontiers in Physics, 2022)
In this paper, a novel refractive index sensor based on photonic crystal fiber and Sagnac ring is studied. The sensor adopts machzand interference principle. The production and experimental steps are as follows: The first step is to fuse the single-mode fiber with the photonic crystal fiber to form a basic sensing unit. The second part uses the coupling birefringence effect of the tapered coupler to fold and fuse the single-mode fiber together to form the Sagnac interferometer. Through this structure, the sensor has the characteristics similar to the polished photonic crystal fiber sensor, while the fabrication complexity is greatly reduced. The refractive index sensing capability and temperature stability of the two structures are analyzed experimentally. Simulation results show that the structure has high birefringence effect. Experimental results show that the proposed photonic crystal fiber combined with Sagnac ring sensor has good sensing performance in the refractive index range of 1.3355 to 1.3560. Compared with the sensor structure without Sagnac ring, the performance is greatly improved, the maximum sensitivity is up to 234 nm/RIU, and it has good temperature stability. The sensor has the advantages of miniaturization, high integration and high sensitivity, and can be used in industry, chemical detection, agriculture and other fields.